POSTOPERATIVE INTRAABDOMINAL ABCESS AND PERITONITIS - M. Kürşat BOZKURT; Savaş TEZEL; S. Hayri GÖZÜBÜYÜK; H. İbrahim DURAL and Şükrü TANER and Y. Selim İLHAN and Seçkin SARI (Turkish Journal of Gastroenterology, 2020)
-